Biodiversity of filamentous fungi coffee beans grown in an organic and conventional system - Couto, Fabiana Aparecida; Couto, Fabiana Aparecida; Monteiro, Mônica Cristina Pereira; Monteiro, Mônica Cristina Pereira; Silva, Daiani Maria da; Silva, Daiani Maria da; Cirillo, Marcelo Ângelo; Cirillo, Marcelo Ângelo; Batista, Luís Roberto (Coffee Science - ISSN 1984-3909, 2013)
The fruits of organically and conventionally produced coffee are subject to contamination from several species of fungi, and that may be related to poor beverage quality and mycotoxin production. The aim of this study was to identify the biodiversity of isolated filamentous fungi in the coffee beans produced on organic and conventional farms within the same area. Two hundred and twelve isolates belonging to eleven different genders were identified from the fifteen samples analyzed. The main gender found was Aspergillus, with isolation of fungi from the Sections Circumdati, Nigri, Flavi and Versicolores. The samples that obtained the greatest index of contamination were those that didn’t pass through the disinfection process with 1% sodium hypochlorite. The samples of coffee beans from organic cultivation exhibited the greatest degree of richness and diversity within a single location with very similar climatic conditions. Thus, organic coffee production requires greater care due to the increased incidence of filamentous fungi.